Manajemen Project Based Learning dalam Meningkatkan Keterampilan Abad 21 di Sekolah Penggerak Jenjang Dasar - Idawati, Idawati; Marsithah, Iis; Yanti, Hera (Universitas Negeri Malang, 2024)
Abstract: This study aims to analyze Project Based Learning planning, Project Based Learning implementation and Project Based Learning evaluation conducted by SD Negeri 21 Bireuen in improving 21st century skills for students and studying the challenges faced in Project Based Learning management. This research uses a qualitative approach with a descriptive method. Data collection through observation techniques, interviews and documentation review. The research subjects were the principal, deputy principal for curriculum, and two class teachers in Phase C. Research results: 1) Project based learning planning has gone well. The activities start from teacher council meetings, socializing project activities to parents. Planning, including: analysis of material characteristics from learning outcomes, determination of goals, conditions, time, compiling steps of project based learning activities, evaluating learning and making worksheets and 6C skill assessment formats. 2) The application of the Project Based Learning model related to improving 6C skills is going well, judging from the steps of activities used according to the procedures of the Project based learning concept. 3) Project based learning evaluation went well. It can be seen from the acquisition of scores on teacher activities to achieve very good predicates, and 4) The challenges faced are that school principals need teachers to be more creative, require a lot of media, costs and time in implementation, so there needs to be breakthroughs and innovations so that the project runs well.Keywords: Management; Project Based Learning; 21st century skills Abstrak: Penelitian ini bertujuan untuk menganalisis perencanaan Project Based Learning, pelaksanaan Project Based Learning dan evaluasi Project Based Learning yang dilakukan oleh SD Negeri 21 Bireuen dalam meningkatkan keterampilan abad 21 bagi siswa serta mempelajari tantangan yang dihadapi dalam manajemen Project Based Learning. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Pengumpulan data melalui teknik observasi, wawancara, dan telaah dokumentasi. Subjek penelitian adalah kepala sekolah, wakil kepala sekolah bidang kurikulum, dan dua orang guru kelas di Fase C. Hasil penelitian: 1) Perencanaan project based learning telah berjalan dengan baik. Kegiatannya mulai dari rapat dewan guru, mensosialisasikan kegiatan project kepada orang tua siswa. Perencanaan, meliputi: analisis karakteristik materi dari dari capaian pembelajaran, penentuan tujuan, kondisi, waktu, menyusun langkah-langkah kegiatan project based learning, evaluasi pembelajaran dan membuat lembar kerja serta format penilaian keterampilan 6C. 2) Penerapan model Project Based Learning terkait peningkatan keterampilan 6C berjalan baik, dilihat dari langkah-langkah kegiatan yang digunakan sesuai prosedur dari konsep Project based learning. 3) Evaluasi project based learning berjalan dengan baik. Terlihat dari adanya perolehan nilai terhadap kegiatan guru mencapai predikat sangat baik, dan 4) Tantangan yang dihadapi yaitu kepala sekolah perlu guru agar lebih kekreatifan, membutuhkan banyak media, biaya dan waktu dalam pelaksanaannya, sehingga perlu adanya terobosan dan inovasi agar project berjalan dengan baik. Kata kunci: Manajemen; Project Based Learning; keterampilan abad 21